(untitled) (Journal of Partial Differential Equations, 2001)
In this paper, the global existence of a unique smooth solution for the Landan-Lifshitz-Maxwell equations of the ferromagnetic spin chain in n(1 ≤ n ≤ 2) dimensions is established by using a coupled priori estimates in Sobolev spaces.